PENGARUH LITERASI DIGITAL, KEAKTIFAN SISWA, DAN KEMANDIRIAN BELAJAR TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA KELAS 5 SD KOMPLEKS DAAN MOGOT - Setia Widowati; Samuel Lukas (LPSDI Bina Patria, 2024)
This study aims to determine the positive influence of digital literacy, student activity, and self-directed learning on students' mathematics learning achievement. The respondents of this study were 152 students who attended SD Kompleks Daan Mogot Tangerang. The research design used was a survey with a deductive quantitative approach. The data analysis technique used was the Microsoft Excel program. The results of the study showed that digital literacy positively influences students' mathematics learning achievement, student activity positively influences students' mathematics learning achievement, and self-directed learning positively influences students' mathematics learning achievement. The research instrument used a questionnaire for independent variables and utilized data from summative assessments for the dependent variable. The validity and reliability tests for the measurement tools used were sufficiently credible. Classic assumption tests were conducted, including frequency distribution, normality test, and regression test for each independent variable with the dependent variable